The Development of E-Modules for Language Politeness Learning in Independent Curriculum-Based Elementary School - Ali Mustadi; Setiawan Edi Wibowo; Octavian Muning Sayekti (Jurnal Kependidikan: Jurnal Hasil Penelitian dan Kajian Kepustakaan di Bidang Pendidikan, Pengajaran dan Pembelajaran, 2023)
This study aims 1) producing a language politeness e-module based on the independent curriculum that is feasible and practical and 2) testing the effectiveness of the language politeness e-module to measure students' mastery of language courtesy at the elementary school level. The method used was Research and Development with the design of the ADDIE development model. This research was conducted on elementary school students in the Special Region of Yogyakarta by considering the category of elementary schools using the prototype curriculum so that the development of this research product is indeed needed as teaching materials for polite language in elementary schools. The sample of the study was chosen using purposive sampling techniques. Research instruments included interview sheets and questionnaires for the analysis of teaching material needs, validation questionnaires for material experts and teaching material experts, interview guideline sheets, and closed questionnaires for media effectiveness tests. Data analysis techniques used descriptive, qualitative-quantitative, and t-test. According to media and material experts, the result of this study was that teaching language politeness based on an independent curriculum was feasible. The average score obtained from the results of the feasibility assessment of material experts I was 4.42 with excellent categories, and media experts 4.6 with excellent categories. The average assessment eligibility score from teachers in product trials included the feasibility of presenting 4.72 with excellent categories, 4.40 with language with excellent categories, 4.90 with displays with excellent categories, and 4.40 with teaching material content conformity with excellent categories. Overall, language politeness teaching materials based on the independent curriculum were declared fit for use after several revisions based on expert advice with an excellent and good final assessment. Teaching materials that are declared suitable for use by teachers so that they can be applied in the learning process in elementary schools.